Aplicação do método de Huffman em compressão de imagem e estudo de métodos Lossless - Cicarelli, Hugo [UNESP] (2018)
In the last years, the number of digital medias has increased exponetially in such a way that Internet's connection speed and storage capacity become a real problem. With that, the theory and application of data compression for these type of data became more significant. In Computer Science, data compression it's the process of encoding the information using fewer bits. On this study, we will approach some techniques of compression, with emphasis in image files, and will be developed an application using one of the studied techniques.